Analysis of AT7519 as a pro-resolution compound in an acetaminophen-induced mouse model of acute inflammation by UPLC-MS/MS - Jennifer A. Cartwright; Joanna P. Simpson; Natalie Z. M. Homer; Adriano G. Rossi (BMC, 2023)
Abstract Background Uncontrolled inflammation contributes to the progression of organ damage in acute conditions, such as acetaminophen-induced acute liver injury (APAP-ALI) and there are limited treatments for this condition. AT7519, a cyclic-dependent kinase inhibitor (CDKI), has been used successfully in several conditions, to resolve inflammation and return tissue homeostatic functions. AT7519 has not been assessed in APAP-ALI and its effect on APAP metabolism is unknown. Targeted chromatography and mass spectrometry can be used to assess multiple compounds simultaneously and this approach has not been applied yet to measure APAP and AT7519 in a mouse model. Results We show an optimised simple and sensitive LC-MS/MS method for determining concentrations of AT7519 and APAP in low volumes of mouse serum. Using positive ion mode electrospray ionisation, separation of AT7519 and APAP and their corresponding isotopically labelled internal standards [2H]8-AT16043M (d8-AT7519) and [2H]8-APAP (d4-APAP), was achieved on an Acquity UPLC BEH C18 column (100 × 2.1 mm; 1.7μm). A gradient mobile phase system of water and methanol was delivered at a flow rate of 0.5 mL/min with a run time of 9 min. Calibration curves were linear, intra-day and inter-day precision and accuracy were acceptable and the covariates of all standards and quality control replicates were less than 15%. The method was successfully applied to evaluate AT7519 and APAP levels 20 h post AT7519 (10 mg/mg) in C57Bl6J wild type mouse serum treated with either vehicle or APAP. Serum AT7519 was significantly higher in mice that had received APAP compared to control, but there was no correlation between APAP and AT7519 quantification. There was also no correlation of AT7519 and hepatic damage or proliferation markers. Conclusion We optimised an LC-MS/MS method to quantify both AT7519 and APAP in mouse serum (50 µL), using labelled internal standards. Application of this method to a mouse model of APAP toxicity proved effective in accurately measuring APAP and AT7519 concentrations after i.p. dosing. AT7519 was significantly higher in mice with APAP toxicity, indicating hepatic metabolism of this CDKI, but there was no correlation with markers of hepatic damage or proliferation, demonstrating that this dose of AT7519 (10 mg/kg) does not contribute to hepatic damage or repair. This optimised method can be used for future investigations of AT7519 in APAP in mice.